Effect of freeze–thaw cycling on the soil‐freezing characteristic curve of five Canadian soils - Ren, J. (2021)
The SFCC is a valuable tool for predicting the hydromechanical properties and for modeling the coupled thermal–hydraulic–mechanical–chemical process in frozen soils. In spite of its importance, the effect of freeze–thaw (F–T) cycling on SFCC has not been well investigated or understood. In this technical note, the effect of F–T cycles on the SFCC of five soils from cold regions of Canada were investigated. The SFCC (including both freezing and thawing branches) of the five soils for different F–T cycles were measured using frequency domain reflectometry (FDR) technique. The experimental results suggest that the effect of F–T cycles on the SFCC of the five soils is not significant. Such a behavior may be attributed to the destruction of soil structure during the saturation process. However, all the five soils’ SFCC exhibited hysteresis behavior for all the F–T cycles. The results of the study are valuable and contribute towards better understanding of the fundamental behavior of SFCC of various cold region soils.